On the Oscillation of Solutions of Differential Equations with Neutral Term - Fatemah Mofarreh; Alanoud Almutairi; Omar Bazighifan; Mohammed A. Aiyashi; Alina-Daniela Vîlcu (Mathematics, 2021)
In this work, new criteria for the oscillatory behavior of even-order delay differential equations with neutral term are established by comparison technique, Riccati transformation and integral averaging method. The presented results essentially extend and simplify known conditions in the literature. To prove the validity of our results, we give some examples.